Study of the process-induced cell damage in forced extrusion bioprinting. (7th June 2021) - Han, Seungsu; Kim, Chul Min; Jin, Songwan; Kim, Taig Young
Abstract: With remarkable developments in technologies, the possibility of replacing injured tissue or organs with artificial ones via three-dimensional bioprinting is being improved. The basic prerequisite for successful application of bioprinting is high cell survival following printing. In this study, numerical calculations and experiments were performed to understand cell damage process incurred by forced extrusion bioprinters. Compressible and shear stresses were presumed to play a pivotal role within the syringe and needle, respectively, based on numerical calculation. To verify the numerical results, two experiments—pressurization in a clogged syringe and extrusion through syringe-needle—were conducted, and the damaged cell ratio (DCR) were measured by live/dead assays. Shear stress of needle flow had a great influence on DCR of discharged bioink, whereas effect of compressible stress in clogged syringe was relatively small. Cell damage in the needle flow is affected by moving distance under load as well as magnitude of shear stress. Applying this concept the differential equation of DCR growing was established, similar to the historied logistic equation for population dynamics, and the mathematical formula to predict DCR was explicitly represented splendidly as a function of only one independent variable, pressure work. The proposed formula was able to effectively predict DCR measurements for 43 bioprinting conditions, and the exactness confirmed the hypothesis for the theory. The presence of safe core zone, which may be related to the critical shear stress and stressed duration on cells, was theoretically conjectured from the DCR measurements, and further studies are necessary for an extensive and profound understanding. Fast printing is required for efficiency of a bio-structure fabrication; however, the higher shear stress accompanying increased operating pressure to speed up bioink discharge rate causes more cell damage. Employing the accurate formula presented, the optimal bioprinting conditions can be designed with ensuring targeted cell viability.